(untitled) (Revista de Ciências Agroveterinárias, 2019)
Since the last decade, the disappearance of pollinating bee populations has been apparent in several countries. This group is responsible for the pollination and maintenance of hundreds of plant species used in human food, in addition to contributing significantly to the socioeconomic development of several communities associated to family farming. In this study, the possible causes of this disappearance are discussed, among which we highlight deforestation, reinforced by the lack of natural flora, inadequate hive management by beekeepers, increasing infestations of pests in the colonies, and the use of agrochemicals. Conservation strategies for native and domesticated bees are suggested, namely: (a) maintenance of the natural landscape that surrounds agricultural areas; (b) beekeepers’ professionalization in the nutritional management and conservation of beehives; and (c) the continuous development of detailed studies about the lethal and sublethal effects of agrochemicals on pollinators.